2022
DOI: 10.3390/healthcare10030440
|View full text |Cite
|
Sign up to set email alerts
|

Change of Direction Speed and Reactive Agility in Prediction of Injury in Football; Prospective Analysis over One Half-Season

Abstract: Agility is an important factor in football (soccer), but studies have rarely examined the influences of different agility components on the likelihood of being injured in football. This study aimed to prospectively evaluate the possible influences of sporting factors, i.e., flexibility, reactive agility (RAG), and change of direction speed (CODS), on injury occurrence over one competitive half-season, in professional football players. Participants were 129 football professional players (all males, 24.4 ± 4.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
2
10
0
1
Order By: Relevance
“…For example, a study on professional ballet dancers showed that the total number of injuries was directly associated with the dancer's age [7]. Similar findings were observed in other sports, for both men and women, where authors regularly reported an increased rate of soft-tissue injuries along with the athlete's age [37,38]. Therefore, our results of higher risk for injury occurrence in older dancers are supportive of some but not all previous studies.…”
Section: Dancers' Age and Injury Occurrencesupporting
confidence: 89%
“…For example, a study on professional ballet dancers showed that the total number of injuries was directly associated with the dancer's age [7]. Similar findings were observed in other sports, for both men and women, where authors regularly reported an increased rate of soft-tissue injuries along with the athlete's age [37,38]. Therefore, our results of higher risk for injury occurrence in older dancers are supportive of some but not all previous studies.…”
Section: Dancers' Age and Injury Occurrencesupporting
confidence: 89%
“…Kelincahan dapat menjadi aspek penting dalam permainan sepak bola (França et al, 2022;Faude et al, 2012). Kelincahan merupakan kemampuan untuk dengan cepat dan akurat mengubah arah gerak seluruh tubuh sebagai respons terhadap suatu stimulus (Mijatovic et al, 2022). Definisi ini didasarkan pada model yang memisahkan kelincahan menjadi dua komponen, kecepatan perubahan arah dan proses persepsi dan pengambilan keputusan (Pojskic et al, 2018).…”
Section: Hasil Dan Pembahasan Hasilunclassified
“…Speed is an asset for athletes who take part in sports that rely on the physical. Several research studies on speed training programs explain the positive impact on athlete performance (Acar & Eler, 2019;Akhmad et al, 2021;Azmi & Kusnanik, 2018;Bullock et al, 2012;Di Domenico et al, 2019;França et al, 2022;Garg & Kadyan, 2016;Mijatovic et al, 2022). This statement needs to be responded to by coaches in the sport of rugby before determining a speed training program.…”
Section: Journal Of Coaching and Sports Science | 71mentioning
confidence: 99%